Landasan Komunikasi dalam Kegiatan Pembelajaran Based Teknologi - Indah Supriani; Heri Nur Cahyono; Ilhami Nurista Pratami; Akif Ardiansyah (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This article is structured to find out about learning media is one means of channeling messages and learning information. Welldesigned learning media, greatly helps learners to digest and understand the subject matter. The development of information technology in the era of globalization and information today, spur the development of learning media progressively advanced as well. Use of Information and Communication Technology (ICT) as a learning medium is already a demand. Although the design of ICT-based media requires special skills, it does not mean the media is avoided and abandoned. ICT-based learning media can be internet, intranet, mobile phone, and CD Room / Flash Disk. Advances in Information Technology has encouraged many changes, including in the field of education that gave birth to the concept of e-learning. With e-learning, the implementation of learning becomes more effective and efficient. E-learning enables learners to be active and creative. E-learning provides educators, educators and educational managers with many benefits, including program flexibility and learning materials that can be made more interesting and memorable. The integration of information technology in education will improve the quality of learning. The impact of follow-up with the integration of information technology in education is to encourage the acceleration of computer literacy in Indonesian society. Utilizing technology as a learning medium in the process of teaching and learning, can facilitate the way teachers in communicating and interacting with students both in the classroom and outside the class. The need for technology in the realm of education is not new, the use of technology to form a conducive and innovative learner . Utilization is proven to play a big role in the smooth process of learning.